Features of frequency of an arterial hypertensia and level of satisfaction of vital needs in various social and economic groups of the population - S. A. Maksimov; V. A. Semenikhin; O. A. Ivanova; Ye. V. Indukayeva; M. Yu. Ogarkov; A. Ye. Skripchenko; G. V. Artamonova (Бюллетень сибирской медицины, 2012)
The role of the professional factor in subjective satisfaction of the basic vital needs (by Mazhnikova N.V. et al., 2001) and frequency of an arterial hypertensia at 791 workers of the enterprises and establishments was studied. It is shown that conditions of labor activity cause distinctions as the general, and separate types of satisfaction of requirements that associates with various level of frequency of an arterial hypertensia.